Comparative Effects of Circuit Weight Training and Interval Weight Training on the Health-Related Physical Fitness Component of Jumpers - Peter Oseremen Oboh (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2023)
This study compared the effects of circuit weight training and interval weight training programmes on jumpers’ health and fitness-related components. The health-related physical fitness components are body composition, cardiovascular endurance fitness, flexibility, and muscular endurance as well as muscular strength. The age of the jumpers ranged from 18 to 21 years, with a mean of 17.9 years. A ten-week training and interval weight training programme was conducted on jumpers that were randomly selected into two experimental groups and a control group. The Analysis of Covariance (ANCOVA) served as the inferential statistics that the study utilised, while the Tukey Pairwise Comparison Test served as the post hoc analysis. The findings of the study revealed that the two training programmes elicited significant changes, but their training effects were not significantly different compared to the health-related physical fitness component of jumpers. It is therefore recommended that both training programmes be utilised by trainers and coaches for conditioning and enhancing the health-related physical fitness components of jumpers for high performance.